ABDULLAH SUNGKAR DAN MASUKNYA PEMAHAMAN SALAFI DI DARUL ISLAM - Zakariah, Irfan (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2022)
Abdullah Sungkar was born in Klaten in 1937. He is of Yemeni descent and lives in Pasar Kliwon. He is active in Al-Irsyad. Abdullah Sungkar has strong religious principles that he learned from his father. He idolized reformist figures both nationally and internationally. After graduating from high school, he continued his father's business. This business led him to meet Abu Bakar Bashir in Jombang. This meeting marked the beginning of his missionary journey. They preached through the radio under the name RADIS (Radio Islam Da'wah Islamiyah) in 1969. Their missionary journey was successful. In 1976, Hispran (Haji Ismail Pranoto) recruited Abdullah Sungkar and Abu Bakar Bashir to enter DI. Abdullah Sungkar and DI have a different understanding. Abdullah Sungkar has a modernist and Salafi Islamic perspective. Meanwhile, DI has a traditionalist Islamic view. The intriguing aspect is the distinction. There are four factors that make salafi not so problematic for DI. First, DI focuses on the ideals of an Islamic state. Second, DI at that time focused on training and recruitment. Third, the spread of salafi understanding is not evenly distributed. Fourth, Abdullah Sungkar was preoccupied with pursuing the authorities. New problems arose when Di was led by Ajengan Masduki and Abdullah Sungkar became foreign minister. Abdullah Sungkar criticized the religious rituals of Ajengan Masduki that contained TBC (Tahayul, Bid'at, and Khurafat). The criticism became a personal matter between the two. Problems reappeared when Ajengan Masduki visited Afghanistan and performed traditional Islamic religious rituals. DI's personal conflicts escalate into major conflicts. Abdullah Sungkar and his followers then declared their departure from DI and continued their ideals through a new organization called Jemaah Islamiyah.